Hubungan Dukungan Keluarga dengan Kepatuhan Pasien Gagal Ginjal Kronik dalam Menjalani Hemodialisa di Ruang Hemodialisa RSUD dr. Slamet Garut - Iwan Shalahuddin; Indra Maulana (STIKes Karsa Husada Garut, 2018)
Hemodialysis is used to treat the end stage renal disease patient or the patient with the chronic disease who needs the immediate dialysis. According to the data taken from Indonesian Renal Registry (IRR) 2011 showed that the number of patient with Chronic Renal Failure (CRF) who conducts the hemodialysis procedure is 22.304. the big problem contribute to the hemodialysis process failure is the patients obedience. There are many factors causes the disobedience of the patients impacting the renal therapy failure, among others age, gender, educational background, HD duration, smoking habit, motivation, health service access, the role of patients perception towards nursing service and family support. The data taken from RSUD dr.Slamet Garut 2014 showed that 66 patients who conducts HD therapy consist of 34 obedient patients and 32 disobedient patients. This research was animed to find out the relationship between family support and Chronic Renal Failure patients abedience who conduct the hemodialysis procedure in Hemodialisa Room RSUD dr. Slamet Garut. The method used in this research was descriptive correlative research method with cross sectional approach. The data analysis used in this research was trough utilizing the univariate analysis with percentage formula and bivariate analysis with Spearman Rank. The result of the research showed that Sig. (2-tailed) was 0,003 less than the critical value α= 0,05 (0,003 < 0,05) means that there is a relationship between family support and Chronic Renal Failure patients obedience who conduct the hemodialysis procedure in Hemodialisa Room RSUD dr.Slamet Garut. There is an intended value that the researcher suggests, it is important that the patient form a group of hemodialysis patient and arrange the follow-up plan in form of reminder card implemented after post hemodialysis procedure in order to remind the next HD.